Couple observational coding systems - Kerig, Patricia; Baucom, Donald H. (Lawrence Erlbaum Associates, 2004)
A companion volume to "Family Observational Coding Systems", this book moves from the triad to the dyad and provides a showcase for significant developments in the coding of intimate couple interactions.